1976
DOI: 10.1530/jrf.0.0470339
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic, pituitary and gonadal hormone production in relation to nutrition in the male hyrax (Procavia capensis)

Abstract: The influence of under-nutrition on reproduction in laboratory and domestic animals, as well as in man, is well recognized, and has been the subject of considerable investigation (see Sadleir, 1969;Howland, 1975). In wild animals, studies on the effects of nutrition on the onset and duration of the mating season and the degree of sexual activity have been mainly restricted to field observations (Verme, 1965;Stodart & Meyers, 1966) rather than experimental investigation.The seasonally breeding rock hyrax (Proca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The increases in plasma SBP which occur in little brown bats during the postnatal and postarousal periods occur at times of rapid increases in body weight (Damassa et ai, 1983 ;. Additionally, studies in other mammals have indicated that food availability can have profound effects on reproductive functions (Delost, 1975;Howland, 1975;Millar & Fairall, 1976;Berger, Negus, Sanders & Gardner, 1981;Kenagy & Bartholomew, 1981;Pirke & Spyra, 1981 ; Eskes, 1983;Nelson, Dark & Zucker, 1983;Barnes, 1984; for earlier references, see reviews by Leathern, 1970Leathern, , 1975. Nevertheless, the results of the present study indicate that the induction of SBP in the little brown bat is independent of changes in food intake or body mass.…”
Section: Discussionmentioning
confidence: 99%
“…The increases in plasma SBP which occur in little brown bats during the postnatal and postarousal periods occur at times of rapid increases in body weight (Damassa et ai, 1983 ;. Additionally, studies in other mammals have indicated that food availability can have profound effects on reproductive functions (Delost, 1975;Howland, 1975;Millar & Fairall, 1976;Berger, Negus, Sanders & Gardner, 1981;Kenagy & Bartholomew, 1981;Pirke & Spyra, 1981 ; Eskes, 1983;Nelson, Dark & Zucker, 1983;Barnes, 1984; for earlier references, see reviews by Leathern, 1970Leathern, , 1975. Nevertheless, the results of the present study indicate that the induction of SBP in the little brown bat is independent of changes in food intake or body mass.…”
Section: Discussionmentioning
confidence: 99%
“…various small mammals indicate that inanition 265 may have consequences for the production and release of gonadotropin hormones (Howland and Skinner, 1973;Howland, 1975;Miller and Fairall, 1976). This paper describes two experiments.…”
Section: Introductionmentioning
confidence: 97%